2018
DOI: 10.1080/13510002.2018.1546985
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated changes in GSH S-transferase gene/proteins in livers of rats

Abstract: Objectives: Glutathione S-transferases (GSTs) are phase-II metabolic enzymes playing important roles in drug metabolism, anti-oxidative stress and anti-aging. Age is a key factor influencing GSTs expression. Thus, age-related changes of 10 GSTs were examined. Methods: Livers from male Sprague-Dawley rats at fetus (−2 d), neonates (1, 7, 14 and 21 d), puberty (28 and 35 d), adulthood (60 and 180 d), and aging (540 and 800 d), were collected and subjected to qPCR analysis. Liver proteins from 14, 28, 60, 180, 54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 34 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…The hepatic GST levels are reported to gradually increase from 2 weeks to 23 months of age in rats [41,46]. Xu et al demonstrated that rat hepatic GST-π protein and mRNA expression continuously increased from 14 days up to 2 years after birth [47], which concurred with the results of our study. GST-π is reported to inhibit JNK phosphorylation by interacting with the C-terminus of JNK [48,49].…”
Section: Discussionsupporting
confidence: 92%
“…The hepatic GST levels are reported to gradually increase from 2 weeks to 23 months of age in rats [41,46]. Xu et al demonstrated that rat hepatic GST-π protein and mRNA expression continuously increased from 14 days up to 2 years after birth [47], which concurred with the results of our study. GST-π is reported to inhibit JNK phosphorylation by interacting with the C-terminus of JNK [48,49].…”
Section: Discussionsupporting
confidence: 92%
“…There are three unique features of the current study: (1) Most of the studies on agerelated changes in hepatic CYPs are performed in mice, (Cui et al 2012;Hart et al 2009;Li et al 2009) this study characterized CYPs and NRs in rats, another commonly-used laboratory animals; (2) Most of the age-related changes in hepatic P450 are focused on the developmental stages to maturation, (Asaoka et al 2010;Bondarenko et al 2016;Cui et al 2012;de Zwart et al 2008;Kilanowicz et al 2015;Park et al 2016) and this study covered the whole life span, and (3) this study extended our efforts to characterize age-and sex-related changes in hepatic drug transporters Zhu et al 2017) and defense mechanisms. Xu et al 2018a;Xu et al 2018b) P450-1 family CYP1 family is responsible for activation of toxicants and drugs. Cyp1a1 is expressed very early in rodents and involved in developmental toxicity of hexachloronaphthalene, (Kilanowicz et al 2015) and immature rats has been proposed as a potential model for chemical risks in children.…”
Section: Discussionmentioning
confidence: 99%
“…Protein antibody complexes were visualized using an Enhanced Chemiluminescent reagent and a ChemiDoc XRS system (Bio Rad Laboratories, Inc., USA). Band intensities were semiquantified by densitometry using Quantity One® software (version 4.6.2, Bio Rad Laboratories, Inc., USA) (Xu et al 2018a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Hines 2013;Saghir et al 2012) Considering the variations of P450 in children, adult, and elderly, this study was initiated to characterize age-associated changes in hepatic P450, to extend our prior work on age-associated changes in hepatic uptake Oatp transporters , efflux MRP transporters. (Zhu et al 2017), the Nrf2 antioxidant pathways, (Xu et al 2018b), glutathione S-transferases, (Xu et al 2018a) and the antioxidant metallothionein gene expression. (Hou WY 2014) The expression of 16 major CYP isoforms, 5 corresponding nuclear receptors (NRs), and 4 phase-II conjugation genes were examined.…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%